Women's Life Writing in the Long 18th Century: A Critical Survey. Issue 1 (January 2015) - Culley, Amy
Abstract This essay provides an overview of developments in studies of British women's life writing in the long 18th century over the last 25 years and explores possible future directions at an exciting moment for the field. It addresses the expansion of the canon under the influence of feminist criticism and the shift in emphasis from autobiography to life writing as a hybrid and indeterminate form which works across disciplinary boundaries. It takes account of scholarly work on traditional categories of women's life writing, such as the scandalous memoir and spiritual autobiography, and considers more recent interests in biography, collective biography, afterlives and the letter. The article concludes with some reflections on potential avenues for future research, including a more rigorous approach to genre, the interrelations of manuscript and print and collaboration and collective authorship, as well as highlighting some of the challenges (and rewards) of working with life writing texts.